ECLIPSE RETINOPATHY: FOLLOW UP OF 36 CASES AFTER APRIL 1995 SOLAR ECLIPSE IN PAKISTAN - Awan, Abdul Aziz; Khan, Tajamul; Mohammad, Sardar; Arif, Abdus Salam (Journal of Ayub Medical College Abbottabad, 2007)
Background: A study was carried out at the Department of Ophthalmology Ayub Medical College, Abbottabad from April 1995 to April 2002 to study the visual acuity changes in patients of solar eclipse retinopathy. Methods: Thirty-six patients with solar eclipse retinopathy were seen. Examination included assessment of Visual Acuity (VA), Slit Lamp examination, Fundoscopy, Fundus Photography and Fundus Fluorescein Angiography where the VA was 6/60. The patients were seen at weekly intervals then at monthly interval and later annually. Results: Poor visual acuity was seen in all patients, after images in 28 patients, Erythopsia in 25 patients and Central Scotoma in 23 patients. Eye involvement was unilateral in 27 cases and bilateral in 9 cases. Twenty-nine patients were male and 7 patients were female. The commonest age group was between 10-30 years. Conclusions: Complete recovery was seen in 26 patients, 7 made partial recovery while in three patients the visual acuity remained poor. Maximum recovery occurred between two weeks to six months. After six months, no changes in the visual acuity or macular lesion were noticed.